Ukuran Perusahaan Memoderasi Pengaruh Kebijakan Hutang terhadap Nilai Perusahaan - Minanari Minanari; Lusia Sri Arini (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study analyzes the impact of debt policy on firm value, considering firm size as a moderating variable in healthcare companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. This research employs a quantitative approach. The data used include financial statements from 34 companies, analyzed using Moderated Regression Analysis (MRA) with SPSS version 25. The results show that debt policy has a significant negative effect on firm value. Firm size, measured by the logarithm of total assets, positively moderates the relationship between debt policy and firm value. This indicates that larger firm size can enhance the effectiveness of debt policy in increasing firm value. These findings provide insights into the importance of considering firm size when formulating debt policy strategies to improve firm value in the healthcare sector